Solar Energy Research at CAZRI, Jodhpur- Achievements and Future Plans - Garg, H P (Annals of Arid Zone, 2016)
Research work on some of the important applications of solar energy for domestic, agricultural and industrial purposes such as for heating of water, drying and dehydration of fruits and vegetables, cooking and boiling of food, distillation of saline water and solar pumping of water for lift irrigation purposes carried out at CAZRI, Jodhpur is reviewed in this paper. Designs of some of the solar energy appliances such as of improved low cost solar water heater are finalised and referred to National Research Development Corporation of India for commercial exploitation. Continuous pre-performance studies of these gadgets were carried out in the field as well as in the laboratory and discussed in this paper.